2013
DOI: 10.3390/cryst3020306
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Betaine Recognition through Cation−π Interactions in Crystal Structures of Glycine Betaine Complexes with C-Ethyl-pyrogallol[4]arene and C-Ethyl-resorcin[4]arene as Receptors

Abstract: Abstract:The glycine betaine (betaine), interacts with several types of proteins with diverse structures in vivo, and in the contact regions, the aromatic rings of protein residues are frequently found beside the trimethylammonium group of betaine, implying the importance of the cation−π interactions in recognition of this molecule. The crystal structures determined by X-ray crystallography of the complexes of betaine and C-ethyl-pyrogallol[4]arene (pyrogallol cyclic tetramer: PCT) and betaine and C-ethyl-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As an example, the use of macrocyclic ligands such as crown ethers 1 calixarenes 2,3 or resorcinarenes 4 for different analytical applications can be mentioned. In this field, the use of pyrogallol [4]arenes as macrocyclic molecules for molecular recognition has made a significant contribution to the development of new applications, including receptors for ammonium salts [5][6][7][8][9] , choline 10 , dopamine 11 , carnitine 12,13 , phosphocholine 14 , betaine 15 and pipecolinic acid among others 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the use of macrocyclic ligands such as crown ethers 1 calixarenes 2,3 or resorcinarenes 4 for different analytical applications can be mentioned. In this field, the use of pyrogallol [4]arenes as macrocyclic molecules for molecular recognition has made a significant contribution to the development of new applications, including receptors for ammonium salts [5][6][7][8][9] , choline 10 , dopamine 11 , carnitine 12,13 , phosphocholine 14 , betaine 15 and pipecolinic acid among others 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Atwood group reported that coordination polymers can be formed using pyrogallol[4]­arene-based metal organic nanocapsules (MONCs) as secondary building units. Pyrogallol[4]­arenes (PgCs) are calixarene-like macrocyclic molecules that are used primarily as supramolecular building blocks in materials constructed through noncovalent means. However, with an upper rim consisting of 12 phenolic hydroxyl groups, these macrocycles can also function as coordinative building blocks in the construction of more complex superstructures. Common structural motifs of PgC-based entities include the hexameric (PgC) 6 M 24 and dimeric (PgC) 2 M 8 MONCs formed with transition metal cations and the infinite-layered networks formed with alkali cations, , among others. , The cage-like coordination complexes formed from transition metal cations are very similar in size and shape to their noncovalently seamed complementary supramolecules , and feature two distinct coordination patterns: eight distinct trimetal clusters in the hexamer and an “octametal belt” in the dimer. , , The coordination number of the metal cations is also different in the two motifs, with tetra- or hexacoordinate sites seen in the hexamer and pentacoordinate sites typically seen in the dimer.…”
Section: Introductionmentioning
confidence: 99%